A comparative analysis of alpha olefin sulfonate and dodecyl sulfate in aphronic fluid containing xanthan gum in a wide range of temperatures - Mohsen Riazi; Abdolhossein Hemmati-Sarapardeh; Mahin Schaffie; Reza Zabihi; Masoud Riazi (Scientific Reports)
Abstract Geothermal energy, oil industry, and underground gas storage technology require deep drilling. Although oil-based drilling fluids have been widely used, they cause environmental issues. Environmentally friendly Aphronic fluid has emerged as an alternative to oil-based drilling fluid. Despite various investigations on Aphron’s performance, the effect of temperature has not yet been comprehensively studied. In this study, Aphronic fluid was developed with xanthan gum (XG) as a polymer and alpha-olefin sulfonate (AOS) as a surfactant. Furthermore, another Aphronic fluid was developed with xanthan gum (XG) as a polymer and sodium dodecyl sulfate (SDS) as a surfactant. This study evaluates their rheological properties, including shear rate (ranging from 0.1 to 10 s− 1), across a range of temperatures (25 ℃, 49 ℃, 71 ℃, and 93 ℃). Stability testing was conducted at ambient temperature, and rheology tests were performed at various temperatures. It was found that the rheological properties decrease as the temperature increases. An increase in the temperature and shear rate decreases the viscosity of the drilling fluid. AOS demonstrated higher stability and less reduction in rheological properties at elevated temperatures than SDS. This difference can be attributed to SDS’s tendency to denature the XG polymer, leading to a notable decrease in viscosity. Maintaining viscosity is crucial for fluid stability and enhancement of rheological properties. Moreover, the best stability was achieved at 1.5 times the critical micelle concentration (CMC). This behavior is consistent with the Gibbs elasticity theory, indicating that the optimal concentration for both AOS and SDS surfactants is 1.5 times the CMC. Deviation from this optimal concentration resulted in decreased system stability. The determination of the CMC value showed a broader region rather than a singular point, potentially confirming the Gibbs-Marangoni theory. The implications of this research underscore the importance of selecting the appropriate Aphronic fluid formula for drilling operations to ensure stability and rheological properties conducive to overcoming reservoir pressure and accurately facilitating the cutting transfer process. This research highlights the need to choose the right Aphronic fluid formula for drilling. Using the right formula helps in drilling to ensure stability and rheological properties conducive to overcoming reservoir pressure and accurately facilitating the cutting transfer process.